A Picture of Family Resilience From the Perspective of Late Teenagers - Widari, Ni Nyoman Tri Puspa; Wulanyani, Ni Made Swasti (Yayasan Sinergi Kawula Muda, 2023)
Family resilience is a very important thing in defending a family. Therefore, this research was conducted in order to be able to understand the picture of family resilience from the point of view of late teenagers. This research used 42 young respondents in Bali who were 20-23 years old with a data collection technique using a questionnaire instrument with an open question type. The result of this research is that there are six characteristics of a resilient family expressed by the respondents, namely a family that is able to survive in any situation as many as 17 respondents (40.40%), a family that is resilient and able to rise up as many as 9 respondents (21.40%), strengthen each other as many as 6 respondents (14.30%), always maintain togetherness as many as 6 respondents (14.30%), maintain and develop intimacy as many as 2 respondents (4.80%), and work together in finding solutions as many as 2 respondents (4.80%).